Comparison of cardiac biomarker dynamics in marathon, semi-marathon and untrained runners: what is the impact on results interpretation? - Goff, Caroline Le; Lennartz, Lieselotte; Vranken, Laura; Kaux, Jean-François; Cavalier, Etienne (Journal of Laboratory and Precision Medicine; Vol 4 (February 2019): Journal of Laboratory and Precision Medicine, 2019)
Background: Cardiac biomarkers elevations have been described after running exercise. Objective of our study was to check cardiac biomarker dynamics in well trained athletes and untrained middle aged apparently healthy men and to highlight the impact on the lab results interpretation in emergency department. Methods: Cardiac biomarkers for ischemic condition, cardiac stretch and fibrotic processes were tested in different type of runners before, directly after and 3 hours after running. Markers for inflammation, muscle disease and renal function were also measured. Results: Cardiac biomarker levels between groups were not statistically different in the pre-exercise samples for natriuretic peptides [B-type natriuretic peptide (BNP), N-terminal Pro BNP (NT-ProBNP)] and galectin-3 (Gal-3), only Troponin I levels were higher. Directly after exercise, all cardiac biomarker levels were higher compared to the baseline, Gal-3 and BNP levels decreased 3 hours after completion of the run. Troponin values continued to increase with highest levels 3 hours after exercise. Troponin T, NT-Pro-BNP and Gal-3 also showed significant correlation to markers of inflammation, fibrosis and renal function. Conclusions: Exercises of different intensity can be associated with biochemical abnormalities and long-term consequences are unknown. In chest pain patients presenting to the emergency department possible impact of exercise on test results, especially Troponin, should be checked.